Fraud in land transaction: conflicting interest between registered proprietor and bona fide purchaser under the national land code 1965 / Noraffy Ahmad, Izzanee Ab Malek Foad and Haidatul Munira Hamzah - Ahmad, Noraffy; Ab Malek Foad, Izzanee; Hamzah, Haidatul Munira (Faculty of Law, 2012)
The numbers of fraud and forgery cases in land transaction are on the rise in Malaysia. Because of that, the issue of conflicting interest between the innocent parties such as the registered proprietor and the bona fide purchaser regarding their rights over the disputed land remains unresolved. It seems that the current Torrens System in Malaysia which applies the mirror and curtain principles as well as the provisions stipulated in the National Land Code 1965 is inadequate to protect the rights of both the registered proprietor as well as the bona fide purchaser with regards to cases of fraud and forgery in land transactions. Realizing this problem, this research paper will examine whether Malaysia can be considered as being at crossroads since it is currently facing a challenge as to whether it should adapt, implement and establish a Trust Assurance Fund as practiced in Canada and Australia in order to guarantee a complete protection for the innocent registered proprietor and bona fide purchaser involved in cases of fraud in land transactions.